2013
DOI: 10.1021/am404276r
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Cytoskeleton and Transient Activation of Ca2+ Channels in Mesenchymal Stem Cells Cultured on Silicon Nanowire Arrays

Abstract: Tissue engineering combines biological cells and synthetic materials containing chemical signaling molecules to form scaffolds for tissue regeneration. Mesenchymal stem cells (MSCs) provide an attractive source for tissue engineering due to their versatility of multipotent differentiation. Recently, it has been recognized that both chemical and mechanical stimulations are essential mediators of adhesion and differentiation of MSCs. While significant progress has been made on the understanding of chemical regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…22 Based on the gene expression data, it was further confirmed that G/SWCNT hybrids could promote osteogenic differentiation and not adipogenic lineage of rMSCs, as evidenced by the upregulation of the osteogenic lineage-associated markers and downregulation of the adipogenic differentiation marker.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…22 Based on the gene expression data, it was further confirmed that G/SWCNT hybrids could promote osteogenic differentiation and not adipogenic lineage of rMSCs, as evidenced by the upregulation of the osteogenic lineage-associated markers and downregulation of the adipogenic differentiation marker.…”
mentioning
confidence: 80%
“…7 In addition to carbon nanomaterials, other types of nanomaterials, such as gold, titanium, silicon, and hydroxyapatite, also exhibit the potential to enhance differentiation. 8,[21][22][23] The earlier studies contain crucial literature as a basis for further exploration of the possible uses of G/SWCNT hybrids for bone repair and regeneration using stem cells.…”
mentioning
confidence: 99%
“…75 The interactions between MSCs and SiNWAs caused the stem cells to preferentially differentiate toward osteocytes and chondrocytes but not adipocytes in the absence of supplementary growth factors. 75 The interactions between MSCs and SiNWAs caused the stem cells to preferentially differentiate toward osteocytes and chondrocytes but not adipocytes in the absence of supplementary growth factors.…”
Section: Effects Of Nanostructure On Cellular Behaviorsmentioning
confidence: 99%
“…For example, mesenchymal stem cells cultured on silicon nanowires show significantly different behaviors of adhesion, proliferation, and differentiation, compared with flat silicon or control substrates. This interaction between mesenchymal stem cells and SiNWs can induce the stem cells to differentiate toward osteocytes and chondrocytes instead of adipocytes in the absence of supplementary growth factors . In addition, Persson et al reported fibroblasts cultured on nanowires exhibiting low motility, impaired cell division, and DNA damage .…”
Section: Physical Approaches For Intracellular Deliverymentioning
confidence: 99%